Variáveis de contorno e loop de Wilson para uma classe de espaços-tempo - Santos, Edinelson Pereira dos (2011)
In thiswork,weinvestigateaclassofspace-timesbycalculatingtheloopvariables for differentcurves,intheparticularcasewherethepathstakenareclosed(circles),we obtain theso-calledholonomytransformations,fromwhichthetraceprovidesthematrix obtained intheWilsonloopgravitational.Firstwediscussthecasewherethegravita- tional fieldisgeneratedbyacylindricalshell,withoutrotation,intheapproximationof weak field.Thenwestudythespace-timesofGödelandFriedman-Robertson-Walker.We also investigatethespace-timesgeneratedbyacosmicstringwithinternalstructure.Fi- nally wediscusstheKottlerspace-timeandsomemodelsofwormholes.Tocalculatethe loop variablesweusetheperturbationexpansiontechnique,whichwecall perturbative method, andtechniquethroughtheLorentztransformationoflocalcoordinates,which we callthe exact method. Theobtainedresultsshowusthewaythesecontourvariables contain informationsrelatedtothegeometricalandtopologicalpropertiesofeachoneof these space-times.